AB0341 SURVIVAL OF REMISSION OR LOW DISEASE ACTIVITY IN RHEUMATOID ARTHRITIS PATIENTS TREATED WITH TOFACITINIB. RESULTS OF RUSSIAN NATIONAL REGISTER. (2nd June 2020) - Gaydukova, I.; Mazurov, V.; Lila, A.; Baranov, A.; Lukina, G.; Babaeva, A.; Kalinina, E.; Salnikova, T.; Sorotskaya, V.; Samigullina, R.; Chakieva, D.; Grabovetskaya, I.; et al.
Abstract : Background: Tofacitinib is an oral Janus Kinase inhibitor for the treatment of rheumatoid arthritis (RA). The survival of remission or low disease activity (LDA) in RA patients, treated with tofacitinib remain unknown. Objectives: To evaluate the survival of DAS28 remission or low disease activity in RA patients treated with tofacitinib. Methods: Data from 102 patients from Russian national register of patients with RA treated with tofacitinib (OREL), achieved DAS28 remission (DAS28<2.6, n=92) or LDA (DAS28<3.2, n=102) were analyzed. Number of patients with increased disease activity, time of disease activation were registered. Statistical analysis performed with statistical programs SPSS2017 and GraphPadPrizm. p-value < 0.05 considered as significant. Results: Baseline characteristics of the patients are presented in table 1 . The remission failed in 45 from 92 patients (48.91%), LDA failed in 65 from 102 of patients (63.72%), table 2 . Proportions of survival of remission or LDA are presented at figure 1 and figure 2 respectively. In 28 from 45 cases of remission failure (62.22%) and in 34 cases from 65 cases of LDA loss (52.3%) the proposal reasons of treatment effect loss were non-medical (absence of reimbursement, changes in patients accommodation, low treatment compliance, etc.). Medical reasons (side effects, inefficacy, etc.) of decrease in remission or LDA survival rate were registered in 17 from 45 cases of remission loss (37.77%) and in 31 from 65 cases of LDA loss (47.69%). Conclusion: On-year survival of remission or low disease activity achieved in Rheumatoid arthritis patients treated with tofacitinib is 51.1% and 36.3 % respectively. The main reasons of treatment efficacy loss were associated with non-medical. Acknowledgments: Pfizer Disclosure of Interests: Inna Gaydukova Grant/research support from: JSC BIOCAD, Speakers bureau: Pfizer, Novartis, AbbVie, JSC BIOCAD, Сelgene, MSD, Sanofi, V Mazurov: None declared, Alexander Lila: None declared, Andrey Baranov Grant/research support from: Bayer, Galina Lukina Speakers bureau: Novartis, Pfizer, UCB, Abbvie, Biocad, MSD, Roche, Aida Babaeva: None declared, Elena Kalinina: None declared, Tatiana Salnikova: None declared, Valentina Sorotskaya: None declared, Ruzana Samigullina: None declared, Diana Chakieva: None declared, Iuliia Grabovetskaya: None declared, Irina Marusenko: None declared, Ekaterina Gaydukova: None declared, Evgeny Nasonov Speakers bureau: Lilly, AbbVie, Pfizer, Biocad, R-Pharm